Organizational Support and Adaptive Performance to Work-Family Conflict - Beni Miprasadi; Adi Rahmat; Bambang Supeno (SAINS ORGANISASI, 2023)
This study aims to identify and explain the mechanism underlying the relationship between organizational support and adaptive performance through work-family conflict variables. This research was conducted at the Regional Secretariat (Setda) of Kuansing Regency where the data was taken from the employees of the Regional Secretariat. The number of respondents in this study was 110 as the research sample. The data analysis techniques in this study were descriptive analysis, convergent and discriminant validity tests, and reliability tests on SEM-PLS analysis. The results of this study indicate that organizational support has a positive and significant effect on adaptive performance, then organizational support has a positive and significant effect on work family conflict and lastly, work family conflict has a positive and significant effect on adaptive performance